Revision of the species of Jaliscoa Bouček within a review of the identity, relationships and membership of Jaliscoa, Catolaccus Thomson, Eurydinoteloides Girault, Lyrcus Walker and Trimeromicrus Gahan (Hymenoptera: Pteromalidae) - Gibson, Gary A. P. (Zootaxa, 2013)
The limits of Lyrcus Walker (1842), Catolaccus Thomson (1878), Eurydinoteloides Girault (1913a), Trimeromicrus Gahan (1914), and Jaliscoa Bouček (1993) are re-evaluated and redefined to better reflect observed distribution of morphological features. Nine of 13 New World species of Catolaccus are transferred to other genera and photographs of the primary type specimens are given to assist future recognition. New features are provided to assist identification of the remaining four Nearctic species of Catolaccus and these are compared to European species, with the observation that C. kansensis (Girault 1917c) could be a junior synonym of C. crassiceps (Masi 1911). Trimeromicrus is removed from synonymy under Lyrcus for the single species T. maculatus Gahan (1914) rev. comb. Newly synonymized under Lyrcus is the Australasian genus Neocylus Bouček (1988) n. syn. Ten species are newly transferred to Lyrcus—L. nigraeneus (Girault 1915) n. comb. (from Neocylus), L. helice (Walker 1843) n. comb. and L. cyaneus (Girault 1911) n. comb. (from Catolaccus), and L. albiclavus (Girault 1917c) n. comb., L. capitis (Burks 1955) n. comb., L. chalcis (Burks 1955) n. comb., L. coeliodis (Ashmead 1896) n. comb., L. deuterus (Crawford 1911) n. comb., L. nigroaeneus (Ashmead 1894a) n. comb. and L. rosaecolis (Burks 1955) n. comb. (from Zatropis Crawford 1908). Catolaccus pallipes Ashmead (1894b) is newly transferred to Pteromalus Swederus (1795) as Pteromalus pallipes (Ashmead) n. comb. and Catolaccus fragariae Rohwer (1934) to Lariophagus Crawford (1909) as Lariophagus fragariae (Rohwer) n. comb. Nine species are newly transferred to Eurydinoteloides—E. tepicensis (Ashmead 1895) n. comb. (from Catolaccus), E. dymnus (Walker 1847) n. comb., E. hermeas (Walker 1847) n. comb., E. incerta (Ashmead 1893) n. comb., E. orontas (Walker 1847) n. comb., E. perdubia (Girault 1916) n. comb., E. platensis (De Santis in De Santis et al. 1979) n. comb. and E. timaea (Walker 1847) n. comb. (from Lyrcus), and E. eudubia (Özdikmen 2011) n. comb. (from Spintherus Thomson 1878). Four species are newly transferred to Jaliscoa—J. grandis (Burks 1954) n. comb. and J. hunteri (Crawford 1908) n. comb. (from Catolaccus), and J. townsendi (Crawford 1912) n. comb. and J. vulgaris (Ashmead 1894b) n. comb. (from Pteromalus). The species of Jaliscoa are revised to include J. nudipennis Bouček 1993, J. bouceki n. sp., J. hunteri and J. vulgaris. Re-established in synonymy under J. hunteri is J. townsendi n. comb. One new species of Pteromalus, P. grisselli n. sp., is described as an egg predator in the egg sacs of Dictyna coloradensi Chamberlin (Araneae: Dictynidae) and compared to Catolaccus species and other pteromalids that are predators of spider eggs. Lectotypes are designated for Pteromalus helice Walker (1843), Catolaccus pallipes Ashmead (1894b) and Catolaccus vulgaris Ashmead (1894b). Diagnoses are given to differentiate Catolaccus, Eurydinoteloides, Jaliscoa, Lyrcus and Trimeromicrus from each other, and more extensive descriptions given to help differentiate these genera from other Pteromalinae. Morphological features are illustrated through macrophotography and scanning electron photomicrography.